Privately owned hospitals - 2015 - Boris Augurzky; Adam Pilny; Ansgar Wübker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
The privatisation of hospitals, i.e. a change in their type of ownership from the municipal and private non-profit type to the private profit-oriented type, has been the subject of heated debate ever since this development began back in the early 1990s. To objectivise this debate, the Fact Books "Significance of Privately Owned Hospitals' were prepared in 2009 and 2012 using data from 2006 and 2009, respectively. The aim was to provide a sound and reasoned assessment of hospital privatisation in Germany by presenting and evaluating relevant key ratios relating to the hospital market, differentiated by type of ownership. The present Fact Book, now in its third edition, has set out to update the analyses performed in 2006 and 2009 to the current data basis from 2012/13. A further aim is to address current debates relating to emergency care and the use of nurses in hospitals. Lastly, the authors wish in particular to shed light on the hospital reform slated for 2015, including both the problem of sustainable investment financing for hospitals and the subject of quality in the hospital.
Keywords: 330